2022
DOI: 10.3390/ijerph191610332
|View full text |Cite
|
Sign up to set email alerts
|

Global Healthcare Needs Related to COVID-19: An Evidence Map of the First Year of the Pandemic

Abstract: The COVID-19 pandemic has exposed gaps and areas of need in health systems worldwide. This work aims to map the evidence on COVID-19-related healthcare needs of adult patients, their family members, and the professionals involved in their care during the first year of the pandemic. We searched the databases MEDLINE, Embase, and Web of Science. Two reviewers independently screened titles and abstracts and assessed full texts for eligibility. Disagreements were resolved by consensus. Descriptive data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…This gap in clinical resources may contribute to increased risk of emotional strain, burnout, post‐traumatic stress and a growing shortage of nurses. In this line of thinking, it will be necessary to continuously assess levels of anxiety, burnout and post‐traumatic stress among nurses, as was prospectively carried out in a number of facilities during the first waves of the pandemic (Aparicio Betancourt et al, 2022; Couper et al, 2022; Gualano et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gap in clinical resources may contribute to increased risk of emotional strain, burnout, post‐traumatic stress and a growing shortage of nurses. In this line of thinking, it will be necessary to continuously assess levels of anxiety, burnout and post‐traumatic stress among nurses, as was prospectively carried out in a number of facilities during the first waves of the pandemic (Aparicio Betancourt et al, 2022; Couper et al, 2022; Gualano et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the results of our study have identified the elements that need to be addressed. The literature's main recommendations are to pay attention to staffing, flexible scheduling, workload, family presence, mental health problems, educational opportunities, leadership support and the creation of healthy work environments which may prevent or reduce burnout (Aparicio Betancourt et al, 2022; Couper et al, 2022; Sharifi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Four ad hoc surveys using open-ended questions were designed by the research team, targeting (1) people with a history of COVID-19 isolated at home, (2) people with a history of COVID-19 who were hospitalized, (3) primary care professionals involved in the care of people with COVID-19, and (4) hospital care professionals involved in the care of people with COVID-19. Surveys were designed based on the healthcare and social-related needs associated with COVID-19 identified after the literature review conducted by our research team ( 14 ), a patient perspective, and the expert opinion of the research team, a multidisciplinary team representing the following disciplines: psychology, speech-language pathology, physical therapy, nursing, medicine, neuroscience, quality improvement, patient safety, and healthcare administration. Each survey consisted of three main sections: Informed consent, sociodemographic questions, and a set of four to six qualitative open-ended questions allowing participants to provide detailed responses related to difficulties, areas for improvement, or unmet needs throughout the patient care pathway, as well as an additional question related to effective strategies and positive aspects.…”
Section: Methodsmentioning
confidence: 99%
“…The unprecedented nature of this novel coronavirus impacted the capacity of health systems to respond to the pandemic rapidly and effectively, with adequate personnel, equipment, medicines, and facilities ( 11 13 ). Limited or inadequate resources and ineffective public health policies, financial instability, and health information and communication challenges, impacted appropriate service delivery, particularly affecting the workforce, patients, and their family members ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of the novel coronavirus in 2019, the virus has spread globally [1,2] and evolved into various variants [3,4], posing a significant challenge to the national healthcare system [5]. Personal protective equipment (PPE) for healthcare workers is unquestionably an important component in the prevention and control of infection during pandemics [6,7].…”
Section: Introductionmentioning
confidence: 99%